Visszaemlékezések 1956 - Szerkesztette és az előszót írta: Berecz János. (Zrínyi Katonai Kiadó, 1986)
Interviews with Antal Apró, Béla Biszku, Gyula Kállai, Valéria Benke, Lajos Czinege, György Nonn, Richárd Nagy, András Berkesi, Gábor Garai, Judit Máriássy, Károly Csémi, Gyula Uszta, György Kőrösi, Sándor Kállai, László Gaál, János Berecz.